Strategi Pengembangan Borobudur Highland melalui Model Bisnis Kanvas dan Inovasi Wisata untuk Menarik Minat Berkunjung Wisatawan - Satria Agus Setiawan Budi Bhakti; Amelda Pramezwary (CV. Creative Tugu Pena, 2024)
Borobudur has become a flagship destination in Indonesia's tourism equality program and designated as a National Strategic Tourism Area (KSPN). To address overtourism, the government is developing Borobudur Highland as an alternative destination, despite facing infrastructure challenges and struggling to attract visitors or investors. This research aims to identify the challenges in managing Borobudur Highland's authoritative land and recommend strategies to increase visitor interest through the canvas business model. The qualitative research methodology focuses on the Borobudur Highland canvas business model to attract visitors, involving in-depth interviews with various stakeholders, observation, and documentation analysis to gain a deep understanding of the case. The findings indicate that overcoming challenges in managing Borobudur Highland's authoritative land requires strategies focused on improved accessibility through robust transportation infrastructure, hosting large-scale events to enhance attraction, developing village tourism to engage local communities, and enhancing amenities such as homestays and Balkondes. These strategies are expected to boost tourist interest and ensure sustainability and economic prosperity in the Borobudur Highland area.